PROBLEMS OF RECOGNITION AND EXECUTION OF FOREIGN JUDICIAL DECISIONS ON FAMILY CASES IN THE REPUBLIC OF KAZAKHSTAN - Kussainov D.U.; Ayupova Z.K.; Beisenbayeva M.T. (Academic Journal of Physical and Chemical Sciences, 2020)
The Republic of Kazakhstan is now at an important stage in the formation of its legal system as a sovereign state. An important role in this process is played by the creation of a normally functioning mechanism of international civil relations, a special component of which is family relations complicated by the “foreign element”. Often, international family relations are accompanied by the problem of recognition and enforcement by one country of the decision of the competent authority on family matters, issued in the territory of another country. Of course, in international family relations it is important that the decision on a family dispute, made by the competent authority of one state, has legal consequences in another state. However, acts of jurisdictional bodies, as a general rule, have a territorial principle of operation. “They acquire legal force in another state if the other state expresses its consent to this in some form.” With regard to family relations, it can be noted that the recognition of foreign decisions in family matters is one of the ways to eliminate “lame family relations,” that is, recognized in the country in which the judgment was issued, but not recognized in the country in which it should give rise to legal consequences.